Comparison of cryotherapy and foam rolling on performance and lactate levels in futsal athletes - Ghea Yolanda Putri, Thirsia; Setiawan, Caly; Hermawan, Rahmat; Ariestika, Elsa (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The use of Cryotherapy and Foam rolling methods is considered to speed up the post-exercise recovery process. However, so far there have been no studies comparing the two methods, thus the aim of this study was to compare the Cryotherapy and Foam rolling methods on performance and lactate levels in futsal athletes. This study uses an experimental method with a one-way crossover design pretest-posttest approach. The total subjects were 16 Amateur Futsal Players with an average age, 20.25 ± 1.23 years; height, 168.87 ± 2.02 cm; and weight, 54.61 ± 1.94 kg; BMI, 19.16 ± 1.01 kg/m-2. The results showed that foam rolling and cryotherapy had no effect on physical performance, but both methods could significantly reduce lactate levels. However, in this case the foam rolling method showed an improvement in the 20-meter sprint which was better than cryotherapy. Thus, the results of this study provide a recommendation for futsal athletes to use foam rolling in the post-exercise recovery process.